Bohm Diffusion in Magnetron Sputtering System: A Review Article - Murad M. Kadhim; Qusay A. Abbas (Iraqi Journal of Industrial Research)
This review provides a comprehensive analysis of recent advances in understanding Bohm diffusion in magnetron sputtering systems, a process critical for optimizing thin-film deposition. Bohm diffusion significantly influences the spatial distribution and energy of sputtered particles near the substrate, impacting the overall film quality and performance. The review delves into theoretical models, experimental findings, and computational simulations to uncover the mechanisms driving Bohm diffusion within the plasma sheath. Key factors, such as magnetic field strength, gas pressure, target-to-substrate distance, and plasma parameters, are examined for their impact on diffusion behaviors and, consequently, film deposition outcomes. By highlighting these interdependencies, the review underscores the importance of Bohm diffusion in achieving controlled, uniform deposition essential for high-performance coatings. Additionally, it addresses how advances in understanding Bohm diffusion can enable more effective tuning of deposition processes to meet specific application requirements in fields ranging from electronics to materials engineering. Through a synthesis of current research, this review offers valuable insights to scientists and engineers aiming to enhance the efficiency and precision of magnetron sputtering for tailored thin-film applications, ultimately contributing to the broader field of thin-film fabrication.